Employment, flexible working and the family - Crompton, Rosemary (The British Journal of Sociology, 2002)
This paper assesses some of the implications of one of the major social changes to have taken place in the West during the second half of the twentieth century — that is, the increased employment of women, together with normative changes in gender relations and in women's expectations. These changes have been linked to an increase in individualism, which itself is associated with the transcendence of ‘first modernity’. Thus it is suggested that new approaches to social analysis are required (Beck). Here it is argued that, rather than develop completely new approaches in order to grasp the changes that are under way, the ‘economic’ and the ‘social’ (that is, employment and the family) should be seen as intertwined, rather than approached as separate phenomena. Past debates in feminism, changes in the family, and flexible employment are critically examined. The growing tensions between employment and family life are discussed. It is argued that these changes are associated with the intensification of capitalist development, rather than reflecting a fundamental transformation of society. Existing approaches to the analysis of social change, including Polanyi's analysis of the development of ‘counter-movements’ against the ‘self-regulating’ market, will, therefore, still be relevant to our enquiries. In the concluding section, a programme of research that would examine these changes is outlined.
Keywords: capitalism; family; flexible employment; gender; modernity

Theorizing the 'Third Sphere': A Critique of the Persistence of the 'Economistic Fallacy.' - Adaman, Fikret; Madra, Yahya M. (Journal of Economic Issues, 2002)
The paper seeks to investigate, from a methodological and ontological perspective, different ways of theorizing the third sphere--the set of activities that can be captured by neither the price mechanism of the markets nor by governmental transactions. The first aim is to elucidate the constitutive elements of the third sphere by deploying Polanyi's forms of integration (reciprocity, redistribution, and exchange). The second is to survey the ontologically individualist and methodologically formalist literature on the third sphere. After elucidating the coexisting sets of behavioral essences in contemporary ontologically individualist and methodologically formalist models of third-sphere activities, the paper claims that this proliferation of behavioral essences can only lead to a methodological impasse. The paper concludes that only with a committed recognition of the heterogeneity of the economy and the endogeneity of the economic subject will it become possible to better grasp the richness of third sphere activities.
Keywords: current heterodox approaches: institutional; economic methodology; economistic fallacy

Anomie, Social Change and Crime - Bernburg, Jon Gunnar (British Journal of Criminology, 2002)
The last decade has seen a revived interest in using anomie theory in crime and deviance research. The present paper contributes to this development by offering an examination of a particular extension of anomie theory, namely, Messner and Rosenfeld's Institutional-Anomie theory. Explicating Institutional-Anomie theory relative to the sociologies of Durkheim, Merton and Polanyi, I find that this theory goes beyond Merton by using a strain of thought that is critical of liberal society. By bringing in the notion of the disembedded market economy, a central notion in the institutionalism of Polanyi and Durkheim, this theory links crime, anomie, and contemporary social change. I also discuss some of the limitations of linking crime with societal level processes in a Durkheimian rather than Mertonian manner.
Keywords: DURKHEIM, Emile; MERTON, Robert; anomie; crime; criminology; disembeddedness

Market Liberalism and Social Protection: Hayek, Durkheim and Polanyi in Theoretical Perspective - Akturk, Sener (Journal of Academic Studies, 2002)
Examines the views of neoclassicist Friedrich A. Hayek, sociologist Emile Durkheim and Karl Polanyi on liberalism. Relationship between the individual, the market economy and society; Features of Hayekian neoclassical economics; Information on Polanyi's book 'The Great Transformation.'
Keywords: DURKHEIM, Emile; Great Transformation, The (Book); HAYEK, Friedrich A. von (Friedrich August), 1899-1992; liberalism; social protection

The Contested Sovereignty of the Firm - Dietrich, Michael (Review of Political Economy, 2002)
This paper suggests that the firm can be analysed as a regulated system of contested sovereignty. The economic literature on the firm is categorised in terms of four different perspectives on sovereignty identified using the twin factors of power and authority. But rather than any single perspective being identified as analytically superior, it is argued that a system of contested sovereignty should be based on all four perspectives. Following this, a Polanyi-inspired analysis of firm regulation is presented in which the regulation of the firm emerges to control the costs of free markets. However, this regulation depicts firm sovereignty as complex and contested rather than simply an optimal response to market failures.
Keywords: business enterprises; economics and literature; firm regulation; firm sovereignty; political economy

The 'new contractualism', social protection and the Yeatman thesis - Gaby Ramia (Journal of Sociology, 2002)
An important characteristic of public policy formulation over the 1980s and 1990s, particularly in the English-speaking countries, has been the increasing use of contractual principles as regulatory tools. The 'new contractualism' represents the recent re-emergence and adaptation of the social contract of the 17th and 18th centuries and the classical legal contract that emerged in the 19th century. The work of Anna Yeatman provides the most cogent and influential, non-neo-liberal scholarly appraisal of the new contractualism. Yeatman argues that the current contractualist agenda is consistent with equality of opportunity, occasioning a redefinition of citizenship so as to improve on the discourse of social protection. This paper argues that any attempt to remove social protection flawed though it is from discussions of the new contractualism is artificial. The social justice implications of such a position are perilous, for policy formulation has not yet entered a phase in which social protection can be superseded in a way which does not violate the rights of the socio-economically disadvantaged.
Keywords: English-speaking countries; YEATMAN, Anna; citizenship; commodity fiction; contractualism; double movement; equality; fictitious commodities; governance; human rights; political planning; social justice; social movements; social protection; sociology

Ecosocialisation and environmental planning: a Polanyian approach - Low, Nicholas (Environment & Planning A, 2002)
Discusses a Polanyian approach to environmental planning, foregrounding the concept of ecosocialization. Global problems of urban modernity; Ecological modernization and the transformation of capitalism; Discussion on ecological Marxism and the transition to socialism; Polanyian perspective for environmental planning.
Keywords: capitalism; environmental engineering; human ecology

Towards a Theory of Values-Based Labeling - Barham, Elizabeth (Agriculture and Human Values, 2002)
An outline of a theory of values-based labeling as a social movement argues that it is motivated by the need to re-embed the agro-food economy in the larger social economy. A review of some basic premises of embeddedness theories derived from the work of Karl Polanyi reveals their connection to particular values-based labeling efforts. From this perspective, values-based labeling presents itself as primarily an ethical and moral effort to counter unsustainable trends within presently existing capitalism. These labels distinguish themselves from ordinary commercial labels by a focus on process and on quality. Evaluating the transformative potential and progressive nature of values-based labeling poses a key challenge. One avenue for gauging this potential is conventions theory. This approach can be adapted to consider the decision making processes that go on within values-based labeling groups, as well as consumer decision making based on such labels, as instances of what is termed a politics of ethical judgment. The conclusion emphasizes the need for more research in this area and suggests how it could be furthered.
Keywords: agricultural policy; agro-food economy; embeddedness; food policy; household production and intrahousehold allocation; marketing; relation of economics to social values; social economy

Transnational Pharmaceutical Corporations and Neo-Liberal Business Ethics in India - D'Mello, Bernard (Journal of Business Ethics, 2002)
The author critiques the expedient application of market valuation principles by the transnational corporations and other large firms in the Indian pharmaceutical industry on a number of issues like patents, pricing, irrational drugs, clinical trials, etc. He contends that ethics in business is chiseled and etched within the confines of particular social structures of accumulation. An ascendant neo-liberal social structure of accumulation has basically shaped these firms' sharp opposition to the Indian Patents Act, 1970, government administered pricing, etc. The author contends that the practice of neo-liberal economics is strongly associated with a "one dimensional" ethics that privileges market valuation principles over all others. This seems to inevitably generate a social counter-movement that struggles for social protections. He critiques neo-liberal business practices from a perspective that derives from the work of the economic anthropologist Karl Polanyi. Before the present phase of liberalization in India, markets were "managed", but without a "welfare state" in place. Moving toward deregulation of the markets without a welfare state in place is unethical. Keeping the debilities of the institutional framework of public policy in mind, the author adopts a Polanyian perspective that places its trust and hope in the growing social legitimacy of the counter-movement in opposition to both neo-liberal business practices and the degenerate behavior of state agencies.
Keywords: India; business ethics; intellectual property; international business enterprises; pharmaceutical industry; socialism

Le bénévolat dans une approche substantive de l'économie, Abstract - Gardin, Laurent (Revue française des affaires sociales, 2002)
RésuméDifférents travaux ont délivré des méthodologies et des données quantifiant l’apport du bénévolat en temps et en argent. Ces préoccupations amènent, dans le sillage des travaux de Karl Polanyi, à appréhender l’économie de manière substantive comme la dépendance de l’homme par rapport à la nature et à ses semblables. Une telle analyse montre qu’il n’y a pas nécessairement une concurrence entre ces différents registres économiques mais qu’une hybridation des ressources peut se mettre en place au service des projets associatifs. Si le bénévolat permet aux pouvoirs publics de faire des économies pour le développement de ces services, il permet aussi de développer des services plus en adéquation avec les demandes sociales, et conduit à une évolution des politiques publiques et à un déploiement de leurs actions pouvant conduire, paradoxalement, à une croissance des dépenses publiques. À partir d’exemples étudiés dans le champ de l’aide aux personnes âgées et handicapées, cette contribution vise à donner les éléments permettant la valorisation du bénévolat, à dresser une typologie des fonctions remplies par le bénévolat et à mesurer son influence sur les différents registres économiques et notamment la redistribution., Various studies have provided methodologies and data for quantifying the contribution of voluntary service in both time and money terms. This work causes one, in the wake of the work by Karl Polanyi, to apprehend the economy in substantive terms – along with the dependence of man compared to nature and his fellow creatures. Such an analysis shows that there is not necessarily a competition between these various economical registers, but that a “hybridization” of resources can be set up in the service of associative projects. If voluntary service makes it possible for the public authorities to make savings when developing such services, it also makes it possible to develop services more in line with social needs, which leads to changes in public policies and to a deployment of their actions, which can lead, paradoxically, to increased public expenditure. This article thus aims to understand the influence of voluntary service on the various economical registers, and in particular on redistribution from examples studied in the field of the assistance to the old and handicapped people, this contribution aims giving the elements allowing the valorization of the voluntary help, drawing up a typology of functions filled by the voluntary help and at measuring its influence on the various economic registers and in particular the redistribution.
Keywords: substantiveness; voluntary service

Proximité spatiale et relations science - industrie : savoirs tacites ou encastrement (Polanyi ou Polanyi) ?, Spatial proximity and relations between academic research and firms : tacit knowledge or embeddedness (Polanyi or Polanyi) ? - Grossetti, Michel; Bès, Marie-Pierre (Revue d’Économie Régionale & Urbaine, 2002)
RésuméLes notions d’encastrement et de savoirs tacites sont souvent utilisées dans des théories expliquant les effets de proximité spatiale dans les relations entre la recherche académique et les entreprises. Même si elles ont des origines proches (ne serait-ce que parce qu’elles ont été formulées à l’origine par deux frères, Karl et Michael POLANYI), elles ont des implications très différentes en ce qui concerne l’interprétation des effets de proximité. Dans un cas (l’encastrement), on peut généraliser l’explication aux effets de proximité dans les relations entre organisations alors que dans l’autre cas (savoirs tacites), l’explication se restreint aux échanges en matière de connaissance. L’analyse d’un corpus de cas de collaboration entre les laboratoires du CNRS et les entreprises plaide en faveur de la thèse de l’encastrement., ENG: The notions of embeddedness and tacit knowledge are often used in the theories explaining spatial proximity effects in the relations between academic research and firms. Even if the two notions have a close origin (they have been defined by two brothers, Karl and Michael POLANYI), they imply different views on spatial proximity effects. In one case (embeddedness), it is possible to generalize the explanation of spatial proximity effects to all kinds of relations between organizations. In the other case (tacit knowledge), only knowledge spillovers can be explained. The analysis of a set of cooperations between firms and french academic laboratories suggests that embeddedness thesis is better.Classification JEL : O18.
Keywords: POLANYI, Michael, 1891-1976; embeddedness; encastrement; proximité; savoirs tacites; science-industrie; tacit knowledge

The World Bank or Polanyi: Markets, Poverty and Social Well-being in Latin America - Kirby, Peadar (New Political Economy, 2002)
Explores the role of markets in achieving social well-being in Latin America, highlighting alternatives theories for this relationship based on the work of Karl Polanyi. Role of markets in reducing poverty; Relation between markets and social institutions; Ways in which market liberalization is damaging the livelihoods of the poor.
Keywords: Latin America; markets; poverty; social institutions

Globalization and Democracy: A New 'Great Transformation'? - Munck, Ronaldo (Annals of the American Academy of Political & Social Science, 2002)
Examines the relationship between democracy and development to set the scene for the pressing contemporary issue of how globalization might affect democracy and vice versa. Reference to the work of Karl Polanyi who posited a dual movement of market expansion matched by increasing social control over it; Impact of globalization.
Keywords: POLANYI, Karl, 1886-1964; democracy; double movement; economic development; globalization

The Construction of Market Institutions in Russia: A View from the Institutionalism of Polanyi - Sánchez-Andrés, Antonio; March-Poquet, José M. (Journal of Economic Issues, 2002)
This article presents information on the construction of market institutions in Russia and includes the institutional conception provided by analyst Karl Polanyi. Polanyi's main ideas will be expounded in regard to his interest in analyzing the transition. These ideas will be adapted to the object of study and then specified so that they will be efficient criteria for analyzing the present economic transition. Second, the results obtained will be applied to the Russian case, and an attempt will be made to draw some conclusions about whether Russia is moving toward a market economy. Although several distinct parts of the work of Polanyi may be of great interest in analyzing the transition process that is occurring in countries that until the 1990s were organized by central planning.. This paper discusses only the aspects which are most closely related to the construction of market economies will be mentioned. According to Polanyi, the commercialization of productive factors and money are among the determining elements for the construction of an economic market.
Keywords: Russia (federation); analysts; central planning; economic reform; industrialization; markets; transition economies